Fundamental Approaches to Software Engineering - Gnesi, Stefania (Springer, 2015)
This book constitutes the proceedings of the 17th International Conference on Fundamental Approaches to Software Engineering, FASE 2014, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2014, which took place in Grenoble, France, in April 2014. The 28 papers included in this volume, together with one invited talk, were carefully reviewed and selected from 125 submissions. They have been organized in topical sections on: modeling and model transformation; time and performance; static analysis; scenario-based specification; software verification; analysis and repair; verification and validation; graph transformation and debugging and testing.